Adolescent Homicides, Suicides, and the Role of Firearms: A Narrative Review. Issue 2 (4th March 2017) - Price, James H.; Khubchandani, Jagdish
ABSTRACT: Background : The United States has more than 90% of all youth firearm deaths that occur in high-income countries.Purpose : We summarize the epidemiological literature on the prevalence, risk factors, and protective factors associated with adolescent homicides and suicides and the role of firearms in the loss of these lives.Methods : A systematic process was used to locate literature on adolescent homicide, adolescent suicide, and adolescent firearm deaths. The literature on these topics was summarized to provide an overview of the issues.Results : Approximately 10% of all arrests in a year for murder and nonnegligent manslaughter are by youth younger than 18 years of age; 92% of these are males. African American male teens are 20 times more likely than white male teens to be victims of homicides. Suicides are attempted more often by adolescent females than males, but males are more likely to die from suicides because they usually use a very lethal method—firearms. Firearms are the implements of choice for adolescent homicides and suicides.Discussion : Too many youth grow up in unhealthy circumstances, faced with a multitude of challenges that contribute to adolescents killing others or killing themselves.Translation to Health Education Practice : Community agencies, parents, and schools need to be proactive in enhancing youth resiliency. This literature review will assist Health Educators in community and school settings to assist communities, families, and youth with creating protective factors to minimize adolescent homicides and suicides.